Characterization of Porous Silica Materials with Water at Ambient Conditions. Calculating the Pore Size Distribution from the Excess Surface Work Disjoining Pressure Model. Issue 12 (15th November 2017) - Georgi, Nikolaj; Kolesnikov, Andrei; Uhlig, Hans; Möllmer, Jens; Rückriem, Michael; Schreiber, Andreas; Adolphs, Jürgen; Enke, Dirk; Gläser, Roger
Abstract: Characterization of mesoporous materials today is routinely performed recording the adsorption isotherm of nitrogen at 77 K. The pore size distribution (PSD) can subsequently be determined using either thermodynamics or statistical mechanics based approaches. While nitrogen has evolved as the reference adsorptive, other gases are often used to extract more information from the isotherm. This contribution is focused on the calculation of a PSD from the water vapor isotherm. It is demonstrated that water adsorption provides accurate results comparable to the standard nitrogen adsorption. Abstract : In contrast to the widely used nitrogen, as a standard adsorptive for characterization of porous materials, it is shown that water vapor at ambient conditions can be used to determine the pore size distribution of silica materials. The presented method provides similar results to the standard method and does not require a reference isotherm.